A STUDY ON THE INVESTMENT BEHAVIOURS AND PREFERENCES OF WORKING PROFESSIONALS IN BANGALORE - V, Prathibha; Pandey, Dr. Pramod Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study explores how working professionals in Bangalore balance income, expenses, savings, and investments, highlighting the gap between traditional perceptions of India as a nation of savers and the nuanced financial realities of individuals. Using a cleaned dataset of over 1,500 professionals and insights from a primary survey, the research finds that income alone does not determine investment potential. While essential expenses remain stable, discretionary spending on lifestyle choices often dictates the capacity to save and invest. Regression analysis shows that high incomes are frequently offset by loan obligations and lifestyle indulgences, whereas moderate earners with disciplined budgeting accumulate wealth more effectively. Survey findings reveal generational differences in investment preferences, with younger professionals gravitating toward fintech-enabled tools and older cohorts preferring traditional instruments.